2015
DOI: 10.1177/1098612x15572035
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings, diagnostics and outcome in 33 cats with adrenal neoplasia (2002–2013)

Abstract: Surgical treatment for feline adrenal tumors (regardless of tumor type) resulted in good long-term survival. Given that pre- and postoperative hypocortisolemia was identified in this study, and, in addition, hypersecretion of more than one adrenal hormone occurred in one cat, adrenal panels prior to surgery may be beneficial as part of the preoperative work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
103
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(109 citation statements)
references
References 38 publications
1
103
1
Order By: Relevance
“…In this small cohort of cats undergoing laparoscopic excision of noninvasive unilateral adrenal neoplasms, only 1 of 7 (14%) cats with complete LA died perioperatively. This result compares favorably with open adrenalectomy, a procedure reported to carry a mortality rate of 26% (14/53 cats) within 2 weeks after surgery . Complications associated with open adrenalectomy include hemorrhage, sepsis, hypotension, pancreatitis, postoperative hypoadrenocorticism, metabolic acidosis, acute kidney injury, lethargy, anorexia, and hepatic lipidosis .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this small cohort of cats undergoing laparoscopic excision of noninvasive unilateral adrenal neoplasms, only 1 of 7 (14%) cats with complete LA died perioperatively. This result compares favorably with open adrenalectomy, a procedure reported to carry a mortality rate of 26% (14/53 cats) within 2 weeks after surgery . Complications associated with open adrenalectomy include hemorrhage, sepsis, hypotension, pancreatitis, postoperative hypoadrenocorticism, metabolic acidosis, acute kidney injury, lethargy, anorexia, and hepatic lipidosis .…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, the treatment of choice for unilateral functional adrenal tumors without evidence of intravascular invasion and metastatic disease is adrenalectomy . The few studies that focus on open adrenalectomy in cats report postoperative complications such as hemorrhage, sepsis, hypotension, pancreatitis, metabolic acidosis, hypoadrenocorticism, lethargy, anorexia, and hepatic lipidosis …”
Section: Introductionmentioning
confidence: 99%
“…10 A retrospective study of 33 cats with adrenal masses identified 17 carcinomas, 13 adenomas and three pheochromocytomas but no cases of lymphoma. 11 The single reported case study of two cats with hypoadrenocorticism as a manifestation of adrenal lymphoma identified multiple sites of metastasis, with evidence such as abdominal effusion or a mass effect present. 10 A retrospective evaluation of metastatic tumors to the adrenal glands in domestic animals identified bilateral masses in 50% of cats, and lymphoma was identified as one of the metastasizing tumors.…”
Section: Discussionmentioning
confidence: 98%
“…Phaeochromocytomas are extremely rare tumours in domestic animals and to the best of the author's knowledge only eight cases of feline phaeochromocytoma are reported in the peer-reviewed literature. [5][6][7] Phaeochromocytomas are often malignant neoplasias, with a median survival time of 20 weeks. 7 Clinical signs are secondary to catecholamine-induced hypertension or due to the presence of a space-occupying mass, and include weakness, collapse, open-mouth breathing, muscle tremors, restlessness, and polydipsia and polyuria.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Phaeochromocytomas are often malignant neoplasias, with a median survival time of 20 weeks. 7 Clinical signs are secondary to catecholamine-induced hypertension or due to the presence of a space-occupying mass, and include weakness, collapse, open-mouth breathing, muscle tremors, restlessness, and polydipsia and polyuria. 5,7 However, hypertension is not always demonstrated as catecholamine secretions may be paroxysmal.…”
Section: Discussionmentioning
confidence: 99%